Baking of Sponge Cake: Experimental Characterization and Mathematical Modelling - Ureta, María Micaela (2015)
Sponge cake is a sweet bakery product that begins as a fluid batter and, during baking, transforms into a porous solid, presenting an important volume expansion. The aim of this work was, first of all, to study experimentally the influence of operative conditions (natural and forced convection; oven temperature, from 140 to 180 °C; steam addition) on volume expansion and the heat transfer dynamics during baking of sponge cake. It was observed that an increase in oven temperature, airflow and steam injection produces an increase in volume expansion. Secondly, a mathematical model was developed to simulate heat transfer coupled with volume expansion. Both experimental and simulated temperature profiles verified that the last region to achieve a correct degree of baking is the one near the crust around the axial axis. In consequence, the minimal baking time was defined as the average time at which this region reaches 95–98 °C. The baking time was strongly affected by the effective oven temperature, with a slight influence of the convection mode.